Towards an Environment-Friendly Animal Feed Industry: The Role of the Nutritionist - Naldo, Michaelito A. (Silliman Journal, 2025)
Feed production is right at the heart of the animal feed supply chain. This supply chain is part of a dynamic global agricultural sector expanding rapidly due to the increasing demand for animal-sourced food, such as meat, dairy products, and eggs. This increasing demand for animal-sourced food results in the increased demand for animal feed, which uses raw materials, i.e., crops, by-products of the food industry, slaughter and processing of livestock, the marine industry, and biofuels, putting greater pressure on natural resources. The animal nutritionist, a major decision-maker in compound feed production systems, takes center stage in selecting and using feed materials, processing, and applying feed products in livestock production systems. This paper identifies the most significant environmental impacts of the feed supply chain and describes the role of the nutritionist in making decisions that could affect these impacts. Improving feed quality through formulation accuracy, increasing crop and animal by-products with the help of exogenous enzymes, and using alternative raw materials with lower life-cycle emissions and impacts were described as strategies nutritionists should adopt to help achieve a more environmentally friendly animal feed industry.